18Fluoride-based molecular imaging of coronary atherosclerosis in HIV infected patients. (March 2020) - Guaraldi, Giovanni; Milic, Jovana; Prandini, Napoleone; Ligabue, Guido; Esposito, Francesco; Ciusa, Giacomo; Malagoli, Andrea; Scaglioni, Riccardo; Besutti, Giulia; Beghetto, Barbara; Nardini, Giulia; Roncaglia, Enrica; et al.
Abstract: Background and aims: Molecular imaging with 18 Fluorodeoxyglucose (FDG) and 18 F-sodium-fluoride (NaF) captures arterial inflammation and micro-calcification and can reveal potentially unstable atherosclerotic plaques. Methods: We performed FDG and NaF PET/CT imaging in two clinically similar cohorts of patients living with HIV (PLWH) with no symptomatic cardiovascular disease. The prevalence and intensity of coronary artery uptake of each tracer, measured as target-to-background ratio (TBR), were assessed in patients at low and high cardiovascular risk. Results: Ninety-three PLWH were submitted to PET/CT imaging with FDG (N = 43) and NaF (N = 50); 42% were at low and 58% at high cardiovascular risk. The intensity of uptake and multivessel coronary artery uptake were significantly higher with NaF than FDG both in low and high-risk patients. When each 18 F-tracer was tested in low and high-risk patients, an equal proportion of subjects showed no vessel, single and multivessel NaF uptake; the same was true for no and single vessel uptake of FDG (no multivessel FDG uptake was noted). Waist circumference, CRP, D-dimer, HIV duration and treatment with nucleoside reverse transcriptase inhibitors were associated with high NaF uptake in univariable analyses; D-dimer remained significant in multivariable analyses (OR = 1.05; p= 0.02). There were no significant associations with FDG uptake. Conclusions: The prevalence of coronary artery uptake was higher with NaF compared to FDG both in high and low risk patients, hence microcalcification imaging may be a more sensitive tool to detect coronary atherosclerosis than inflammation imaging. However, the uptake of each 18 Fluoride tracer was similar between low and high-risk subjects, and this underscores the discordance between clinical and imaging based risk assessment. Future investigation should address the prognostic significance of NaF coronary artery uptake. Graphical abstract: Image 1 Highlights: In HIV infected patients there was a higher prevalence of coronary artery uptake of 18 F-Sodium Fluoride than 18 Fluoro-deoxyglucose. The uptake of each 18 F-based tracer was similar between high and low risk patients. This highlights the difference between clinically defined risk and imaging markers of atherosclerosis.